Anthrax Epidemıc Management in an Eastern Turkey Region - Akbulut, Ayhan; Tanır, Büşra; Tartar, Ayşe Sağmak; Balin, Şafak Özer; Şahin, Mitat (Hamadan University of Medical Sciences, 2024)
Background: Anthrax is a zoonotic disease caused by Bacillus anthracis. It has been known for centuries and remains hyperendemic in certain parts of the world, with occasional epidemic outbreaks. This study aimed to investigate an anthrax outbreak affecting a family and their close contacts in the Akçakiraz town of Elazığ province in eastern Turkey. Methods: Twenty-two individuals who had contact with a sick animal in Akçakiraz were included in the study. Weekly anamnesis, physical examinations, and follow-ups were conducted over three weeks. Swab samples were collected from the wound sites of hospitalized patients for culture and Gram-staining. Blood and wound samples were sent for polymerase chain reaction (PCR) analysis to detect B. anthracis. A sample was taken from the liver tissue of the infected animal. Statistical analysis was performed using SPSS 25. Results: Of the 22 individuals, 9 (40.9%) were hospitalized and treated, while 13 (59.1%) were monitored on an outpatient basis. B. anthracis spores were identified in Gram-stained samples from the liver of diseased animal. PCR positivity for B. anthracis was detected in the wound samples of two patients (22.2%), although the PCR results from the blood samples of these patients were negative. No bacterial growth was observed in wound cultures, and gram-staining did not reveal any notable features. All patients were successfully treated. Contacts, family members, and residents were informed and educated about the disease, and necessary public health measures were implemented through coordination with the Provincial Hygiene Board. Conclusion: Increasing awareness of zoonotic diseases, especially anthrax, is essential. It is crucial to implement societal prevention measures, including controlling animal production, educating at-risk populations in endemic areas, vaccinating animals, preventing contact with sick or deceased animals, and preventing environmental contamination by decontaminating affected areas. © 2024 The Author(s).
Keywords: Anthrax; Bacillus anthracis; Epidemic